2007
DOI: 10.1007/s00405-007-0290-4
|View full text |Cite
|
Sign up to set email alerts
|

Papillary thyroid microcarcinoma: incidence and prognostic factors

Abstract: The objective of this study was to define the prognostic factors of papillary microcarcinoma of the thyroid (PMCT), and to analyse their epidemiologic and histopathologic characteristics. Our series included 57 patients diagnosed with PMCT between 1994 and 2003 among 944 patients who underwent thyroid surgery. All the surgical specimens were examined in the same department of pathology using the same technique. The prognostic factors were elaborated from the results of the histological examination. The epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 14 publications
5
16
1
Order By: Relevance
“…4,10,36,38,[41][42][43] In contrast, in studies in which multifocal or all PTMC patients were given central neck dissection, there was no statistical difference in local recurrence between multifocal and unifocal tumors. 22,25,27,44 Routine neck dissection eliminates the possibility of residual micrometastases in high-risk cases with LNM, which may explain the above phenomenon.…”
Section: Discussioncontrasting
confidence: 46%
“…4,10,36,38,[41][42][43] In contrast, in studies in which multifocal or all PTMC patients were given central neck dissection, there was no statistical difference in local recurrence between multifocal and unifocal tumors. 22,25,27,44 Routine neck dissection eliminates the possibility of residual micrometastases in high-risk cases with LNM, which may explain the above phenomenon.…”
Section: Discussioncontrasting
confidence: 46%
“…Histopathological characteristics such as the vascular infiltration, extension to the adjacent parenchyma or the thyroid capsule, multiple foci, are all associated with metastatic spread, which may explain the above-mentioned results. 34,35 …”
Section: Discussionmentioning
confidence: 99%
“…Total/near total thyroidectomy was carried out in 100% of the cases in 17 (11,12,14,15,18,24,26,27,39,46,49,52,97,104,106,117,150) out of 44 studies that reported the type of surgery (4-6, 8, 11, 12, 14-18, 20, 23-27, 30-32, 34, 38-40, 42, 45, 46, 48-50, 58, 97, 98, 104-106, 114, 117, 121, 123, 124, 143, 148, 150). Combining the results of different studies that clearly reported the extent of surgery in 9259 patients with PTMC, total/near total thyroidectomy was performed in the 72%, subtotal thyroidectomy in the 11% and lobectomy in the 17% of the cases (4-6, 8, 11, 12, 14-18, 20, 23-27, 30-32, 34, 38-40, 42, 45, 46, 48-50, 58, 97, 98, 104-106, 114, 117, 121, 123, 124, 143, 148, 150).…”
Section: Surgical Proceduresmentioning
confidence: 99%